Keberagaman Gender Dewan Komisaris dan Direksi terhadap Kinerja Perusahaan - Thoomaszen, Sinye Polani; Hidayat, Widi (E-Jurnal Akuntansi, 2020)
This study examined the influence of board gender diversity on the firm performance.the research sample use property and health companies listed in Indonesia stock exchange 2015-2018. total 30 companies. use quantitative methodology with panel regression data analysis techniques were used in this study. The results showed that the gender diversity of the board of commissioners did not have a positive effect on company performance (H1 was rejected) while the gender diversity of the board of directors had a negative effect on company performance (H2 rejected). SIZE and ID control variables also showed significant effect on company performance. For further research it is recommended to use two other methods such as Dummy or gender proportion to measure gender diversity so that the results can be compared, as well as more research data. Keywords: Board Gender Diversity; Firm Performance; Size; Independen Director.